2003
DOI: 10.1086/374980
|View full text |Cite
|
Sign up to set email alerts
|

Emission‐Line Spectra of Arix–Arxviin the Soft X‐Ray Region 20–50 A

Abstract: As part of a larger project to complete a comprehensive catalog of astrophysically relevant emission lines in support of new-generation X-ray observatories using the Lawrence Livermore electron beam ion traps EBIT-I and EBIT-II, we present observations of argon lines in the extreme-ultraviolet region. Our database includes wavelength measurements with standard errors, relative intensities, and line assignments for Ar ixAr xvi between 20 and 50 Å . The experimental data are complemented with a full set of calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
94
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 23 publications
(24 reference statements)
7
94
1
Order By: Relevance
“…(a) Sources of NIST v3 are from the unpublished work of Shirai et al (1999), and references therein, while that of CHIANTI v6 is from the work of Lepson et al (2003).…”
Section: Notesmentioning
confidence: 99%
“…(a) Sources of NIST v3 are from the unpublished work of Shirai et al (1999), and references therein, while that of CHIANTI v6 is from the work of Lepson et al (2003).…”
Section: Notesmentioning
confidence: 99%
“…In Table 2 Table 2. Therefore, a larger calculation has become necessary, especially when some of the observed emission lines belong to the 4 levels -see Table 6 of Lepson et al (2003).…”
Section: Ar XIVmentioning
confidence: 99%
“…A complete list of lines over a wide range of wavelengths for many ions, including those of argon, are available in the  database at http://wwwsolar.nrl.navy.mil/chianti.html. Additionally, to provide experimental support to observational data, many lines of Ar IX−XVI in the 20−50 Å X-ray range have been measured in the electron beam ion trap () experiments of the Lawrence Livermore National Laboratory (Lepson et al 2003). …”
Section: Introductionmentioning
confidence: 99%
“…For example, Audard et al (2001) demonstrated the discrepancies between modelling and the XMM-Newton observation for Capella, in particular emission lines in range of 20−38 Å. In modelling laboratory spectroscopy of highly-charged argon and sulphur with the Hebrew University Lawrence Livermore Atomic Code (HULLAC; Bar-Shalom et al 1988), Lepson et al (2003Lepson et al ( , 2005 demonstrated that there are large discrepancies between the laboratory measurements and the HULLAC simulation. Liang et al (2008b) reported a line list for highly charged Si ions including Si X, and their comparison with observed values for the Procyon corona showing discrepancies.…”
Section: Introductionmentioning
confidence: 99%